Analisis Nilai Moderasi Beragama pada Serial Nussa dan Rara serta Relevansinya dengan Pembelajaran Agama Islam Kelas IV Sekolah Dasar - Fitama, Diko Nasrul; Andrian, Firma; Annisah, Siti; Adiwijaya, Satria Nugraha; Wibowo, Rahmad Ari (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
Indonesia's diversity is the main cause of social conflict both verbally and psychologically. Social conflicts that occur in everyday life can certainly bring Indonesia into the abyss of misery. So religious moderation education needs to be integrated into education. The implementation of religious moderation education at an early age, especially in elementary school, is the basic foundation for creating a sense of unity and integrity in Indonesia. This research aims to analyze the values of religious moderation in the Nussa and Rara series and their relevance to Islamic religious learning. This research method uses a literature study, with data collection techniques reviewing documents on the Nussa and Rara video series. The data analysis technique in this research uses detailed qualitative descriptions in the Nussa and Rara video series. The findings in this research show that the value of national commitment is found in the episode